Interpreting Sustainability through the Lens of Generation Z: A Study of Hotel Experiences in Nusa Dua - Putra, Putu Pendy Amdika; Putra, Putu Candra Ardiana (Jurnal Ilmiah Hospitality Management, 2025)
Sustainability has become an influential factor shaping tourist behavior and hospitality marketing practices worldwide. Framed through the Triple Bottom Line, which integrates environmental, social, and economic dimensions, this study examines Generation Z’s perceptions of sustainability in the Nusa Dua hotel context using a phenomenological approach. Five informants aged 22–26 were selected through purposive sampling based on their prior stays in sustainability-oriented hotels, with data collected via in-depth interviews. The findings indicate that Generation Z perceives sustainability as an extension of an environmentally conscious lifestyle closely linked to social responsibility and generational identity. Participants emphasized the importance of transparency and authenticity in hotel operations, particularly in communicating resource management practices. Digital tools, such as smart-room technologies and app-based controls, were viewed as critical in enabling intuitive conservation behaviors. Moreover, Generation Z expects credible storytelling, meaningful community engagement, and innovative digital solutions to enhance sustainable stay experiences. This study offers practical insights for hotel managers seeking to engage Generation Z, while reinforcing the relevance of the Triple Bottom Line framework in contemporary hospitality research.